An improvement of Interactive Prioritization Technique for Requirements Interdependency in prioritization process - Siti NurSyafiqah, Rusli; Rohani, Abu Bakar; Siti Suhaila, Abdul Hamid (IEEE, 2023)
Requirement Prioritization (RP) was introduced as a solution to the project with huge number of requirements by eliminating some of the requirements based on fair judgement in terms of priority value or rank made by expertise or stakeholder or both parties depending on the technique's specific operation. Along with the RP concept, there is another concept that must be deeply understood, which is Requirement Interdependencies (RI), which describes the interdependencies of requirements with each other. However, not many RP techniques involve the RI element during the RP process, citing complexity as the key reason for this, even though the RI element plays a critical role in determining the most important requirement for improving the project success rate. This paper describes the proposed technique, which improves the RP process while considering the RI element. Two conventional RP techniques, Three-level Scale and Rank Ordering. Each RP technique plays an important part in producing high accuracy results while improving the impact of RI element during the RP process.